Implementasi Kebijakan “Tabu Beusaree Hase Meulimpah” dalam Pencegahan Gagal Panen di Kabupaten Nagan Raya - Pratama, Agus; Macella, Agatha Debby Reiza; Mardhiah, Nellis; Jonsa, Alimas (Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Riau, 2024)
This research aims to find out how the policy on planting patterns and rice field harvesting schedules is implemented simultaneously with the philosophy of